The Global Impact of Brexit Uncertainty - HASSAN, TAREK A.; HOLLANDER, STEPHAN; LENT, LAURENCE VAN; TAHOUN, AHMED (Journal of Finance, 2024)
ABSTRACT We propose a text‐based method for measuring the cross‐border propagation of large shocks at the firm level. We apply this method to estimate the expected costs, benefits, and risks of Brexit and find widespread reverberations in listed firms in 81 countries. International (i.e., non‐U.K.) firms most exposed to Brexit uncertainty (the second moment) lost significant market value and reduced hiring and investment. International firms also overwhelmingly expected negative first‐moment impacts from the U.K.'s decision to leave the European Union (EU), particularly related to regulation, asset prices, and labor market impacts of Brexit.